Matemática e afetividade: relações e enunciações de acadêmicos e egressos dos cursos de Licenciatura em Matemática e Pedagodia da UFSM - Lara, Jenifer Laís de (2023)
Affection, by being imbricated in the teaching and learning process, can improve learning and linking Mathematics. Considering that, at any level of education, one works with human beings in constant development, in which emotions and affections are present in the classroom, it is essential to work with an affective bias. Affectivity in the sense of openness to dialogue, to the exchange of ideas and experiences and respect for all subjects within the classroom. The present study has as its research problem the question “How/or if the theme of affectivity is placed in the initial academic training of theachers (or future teachers) who teach Mathematics in Basic Education, and what the understandings of students from the Licentiate Degree in Mathematics and Pedagogy at the Federal University of Santa Maria, regarding the affective relationships built in the classroom, whether in a face-to-face or virtual teaching environment?”. To answer this question, the objective is to investigate how the theme of affectivity is present in the initial training of theachers who teach Mathematics in Basic Education, and observations of academics and graduates of aforementioned courses. As a theoretical framework, this study was based on the principles of Lev Vygostky, a pioneer in human development studies with a perspective on affectivity, as well as those of Leite and Tassoni, more contemporary scholars who highlight the affective perspective in Education. Through the qualitative approach, the methodology followed the analysis of the Curricular Projects of the UFSM Courses, the realization of interviews with the academics and their graduates, who volunteered and, finally, the opinions of these subjects regarding the themes involved were discussed. It was concluded that the theme of Affectivity is very little addressed in research, as well as rarely mentioned in the guiding documents of the courses. The interviewees, in their statements, did not remember having seen the theme worked on in the classroom. However, all of them pointed out that the good relationships built there can facilitate the learning of Mathematics.